The sea-ringed world : sacred stories of the Americas - García Esperón, María (Lantern Paperback, 2022)
Contains a collection of short stories of Native American myths and legends from tribes and cultures throughout all of the Americas. Includes a transcription of Indigenous terms, a pronunciation guide, a map, and a glossary.